Accessory cavitated uterine malformation: an underdiagnosed Mullerian anomaly - Elhabashy, Ahmed; Elhabashy, Moustafa; Salem, Hassan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Accessory cavitated uterine malformation (ACUM) is an extremely rare Mullerian anomaly that is not yet classified by the international societies as a type of uterine malformations. Due to its rarity, it is usually misdiagnosed as adenomyoma. Objective was to provide specific sonographic features of ACUM and differentiate it from the more common adenomyoma. Methods: Our study is a comparative retrospective study. We presented the sonographic features of 3 cases of ACUM and compared these features with the sonographic features of 10 cases of adenomyoma. All cases had scanned by 2D and 3D luteal TVUS at Habashy 4D scan centre (Alexandria; Egypt) between June 2019 and June 2024. All the 13 cases in our study were had chronic pelvic pain and dyspareunia with a lesion in the myometrium that was not matched with the whorly echotexture of myoma. We had described the sonographic characteristics of the lesion and matched them with the final diagnosis after histopathology. Results: TVUS features of the 3 cases who had ACUM were cystic lesion within the lateral myometrial wall. Its content has ground glass echotexture. TVUS features of the 10 cases of adenomyoma were heterogeneous ill-defined solid myometrial lesion with translesional minimal flow. Conclusions: ACUM is a rare uterine malformation that is usually misdiagnosed as adenomyoma. Distinction between these two pathologies is important as the treatment of both differ. ACUM is suggested in patients with pelvic pain when there is a myometrial cystic lesion separable from a normal uterine cavity and contained a ground-glass material.